Lack of registration of information on the application for traction on the subject of encumbrance as a change, which excludes the possibility of recovery under the writ of execution of the notary - Vovk, Yu (Науковий вісник Ужгородського національного університету. Серія Право, 2022)
The article deals with problematic issues related to the execution of notaries of inscriptions. It is noted that the number of concluded credit agreements is drawn up every year. The share of non-performing loans is also growing. In case of late repayment of funds by the borrower, it is possible to apply to the court or a notary with the use of funds and receive interest on the loan. In this case, to a large extent there is a possibility of collecting the relevant funds under the writ of execution of the notary. The notary makes inscriptions to the executor if the submitted documents confirm the indisputability of the debt or other liability of the debtor to the debt collector and provided that no more than three years have passed since the date of the claim. It is emphasized that the problem with this problem is that the current legislation does not define an exclusive list that indicates a dispute over debt. It is noted that in case of consideration of the case in court, these circumstances must be established in court. In this case, such a procedure that excludes the possibility of foreclosure on the executor of the notary's inscription on the removal of foreclosure on the subject of encumbrance. It is noted that the Grand Chamber of the Supreme Court in this matter ensures the unity of judicial practice of courts of commercial and civil jurisdiction. Emphasis is placed on the fact that, taking into account the judiciary, a notary public practitioner has no right to make a writ of execution if the encumbrancer does not comply with the Law «On securing creditors' claims and registration of encumbrances». A prerequisite is the receipt of the debtor's breach of the secured encumbrance by the association's obligations, as well as the mandatory registration in the Register of information on the recovery of the security association. It is important to comply with the 30-day period from the moment of registration in the Register of information on the application for recovery for security encumbrances. In general, the notary's observance of all the necessary formalities does not allow the notary to recognize the writ of execution as unenforceable.